The impact of reverse logistics towards sustainable environment - Azaman, Ernee Nor Fatihah; Abdullah, Rohani (2012)
The purpose of these studies is to briefly review the recent literature and to determine the impact of reverse logistics towards a sustainable environment.Many companies first focused on reverse logistics issue because of environmental concern.In the future, environmental considerations will have a greater impact on many logistics decisions.This study focuses on four activities in reverse logistics to determine the impact of reverse logistics for the environment such as recycle, returnable product, reusable, source reduction, using environmental friendly product, and to determine the activities give a most impact of environment.